2020
DOI: 10.3390/met10030353
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Aging Treatment on Microstructure and Tensile Properties of a Hot Deformed UNS S32750 Super Duplex Stainless Steel (SDSS) Alloy

Abstract: In this present study, the influence of isothermal aging temperature and duration on microstructural and mechanical properties of a hot-deformed UNS S32750 super duplex stainless steel (SDSS) alloy was investigated by SEM-EBSD (scanning electron microscopy-electron backscatter diffraction) and tensile testing techniques. An isothermal aging treatment, at temperatures between 400 and 600 °C and treatment duration between 3 and 120 h, was applied to a commercial UNS S32750 SDSS alloy. Microstructural characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…So, considering the 1040 °C solution annealing temperature and ageing temperature variation, with an increasing temperature from 950 °C to 1050 °C, yield strength and ultimate tensile strength decrease, and correspondingly, total elongation and product of strength and elongation values are increased, Table 3. It indicates that higher ageing temperature increases the release of the stored energy during the cold working and thereby leads to an enhanced ductility, a better combination of strength and ductility but a decrease in the strength which is suited for formability applications [5, 11, 14]. Similar trends were evident for the samples that underwent various processing after hot deformation and solution treatment at 1300 °C.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…So, considering the 1040 °C solution annealing temperature and ageing temperature variation, with an increasing temperature from 950 °C to 1050 °C, yield strength and ultimate tensile strength decrease, and correspondingly, total elongation and product of strength and elongation values are increased, Table 3. It indicates that higher ageing temperature increases the release of the stored energy during the cold working and thereby leads to an enhanced ductility, a better combination of strength and ductility but a decrease in the strength which is suited for formability applications [5, 11, 14]. Similar trends were evident for the samples that underwent various processing after hot deformation and solution treatment at 1300 °C.…”
Section: Resultsmentioning
confidence: 58%
“…Further addition of nitrogen improves weldability and slows down the formation of intermetallic phases, due to its austenite stabilizing characteristics, it maintains a proper ferritic and austenitic balance and improves the corrosion resistance [1, 12–14]. In addition, nitrogen provides structural hardening via interstitial solid solution strengthening and increases yield strength and ultimate tensile strength without altering the toughness [2, 7, 11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The properties of duplex stainless steels (DSSs) depend on the ferrite-austenite ratio and on the contents of secondary phases [1]. The actual phase content depends on the chemical composition of the steel, and heat treatment of the final product [2]. Therefore, it is necessary to control the volume fractions, morphologies, and distribution patterns of all phases.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the two most influential occurring phenomena are represented by the stress relief and the secondary phase precipitation. In the second one [10], the effect of controlled cold rolling on the microstructure and mechanical properties of the rare earth Ce-modified superduplex stainless steel was investigated. It is shown that with the increase in deformation, the strength of Ce-modified superduplex stainless steel increases rapidly and the elongation decreases dramatically.…”
Section: Introductionmentioning
confidence: 99%